2023
DOI: 10.1021/acsomega.3c01497
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Selenium(IV) Oxidation by Aqueous Bromine Solution

Abstract: The bromine−selenite reaction at strongly acidic conditions was investigated by monitoring the absorbance−time traces at the isosbestic point of the bromine−tribromide system at a constant ionic strength (0.5 M adjusted by sodium perchlorate) and temperature. Despite the simplicity of the stoichiometry, the kinetics was found to be very complex. Although the formal kinetic orders of the reactants bromine and selenite are strictly 1, that of the hydrogen ion varies from −2 to less than −3 and notably depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The kinetics of eq 4 was found to be very complex, recently an overall model was proposed to describe all the characteristic features of this reaction including hydrogen and bromide inhibited pathways. 15 It was also demonstrated that this mechanism is capable of explaining the pH-dependence of the reaction at the pH range of 1−13. Therefore, here, we directly implemented it in the proposed model without any simplification to preserve all the characteristics of the selenite−bromine reaction.…”
Section: ■ Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The kinetics of eq 4 was found to be very complex, recently an overall model was proposed to describe all the characteristic features of this reaction including hydrogen and bromide inhibited pathways. 15 It was also demonstrated that this mechanism is capable of explaining the pH-dependence of the reaction at the pH range of 1−13. Therefore, here, we directly implemented it in the proposed model without any simplification to preserve all the characteristics of the selenite−bromine reaction.…”
Section: ■ Resultsmentioning
confidence: 96%
“…The kinetics of eq was found to be very complex, recently an overall model was proposed to describe all the characteristic features of this reaction including hydrogen and bromide inhibited pathways . It was also demonstrated that this mechanism is capable of explaining the pH-dependence of the reaction at the pH range of 1–13.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations